Morphologic abnormalities in potassium-deficient dogs. - Tate, C. L. (1978)
Potassium deficiency was produced in 16 dogs by means of a diet containing less than 0.03% potassium. Decreases in serum potassium were first observed after 3 weeks. Morphologic changes occurred only in heart, skeletal muscle, and kidney. Focal myocardial necrosis was observed in 6 of 16 deficient dogs, and skeletal muscle degeneration and necrosis were observed in 14 of 16 deficient dogs. A complex nephropathy consisting primarily of epithelial hypertrophy and hyperplasia in the collecting tubules of the inner stripe of the outer medulla occurred in all the deficient dogs.